Getmanets M. F. Unrecognized theoretical literary term - Getmanets M. F. (Philological Treatises, 2020)
Necessity and truthfullness of the formation of a theoretical-literary category “mass character” is grounded in the article. The author throws light upon the discussion of this issue, gives opinions of L.Tolstoy and other writers. Also he refers to the practice of creative work.